Life-Cycle Assessment of the Wastewater Treatment Technologies in Indonesia’s Fish-Processing Industry - Shinji Takeshita; Hooman Farzaneh; Mehrnoosh Dashti (Energies, 2020)
In this paper, a comprehensive life-cycle assessment (LCA) is carried out in order to evaluate the multiple environmental-health impacts of the biological wastewater treatment of the fish-processing industry throughout its life cycle. To this aim, the life-cycle impact assessment method based on endpoint modeling (LIME) was considered as the main LCA model. The proposed methodology is based on an endpoint modeling framework that uses the conjoint analysis to calculate damage factors for human health, social assets, biodiversity, and primary production, based on Indonesia’s local data inventory. A quantitative microbial risk assessment (QMRA) is integrated with the LIME modeling framework to evaluate the damage on human health caused by five major biological treatment technologies, including chemical-enhanced primary clarification (CEPC), aerobic-activated sludge (AS), up-flow anaerobic sludge blanket (UASB), ultrafiltration (UF) and reverse osmosis (RO) in this industry. Finally, a life-cycle costing (LCC) is carried out, considering all the costs incurred during the lifetime. The LCA results revealed that air pollution and gaseous emissions from electricity consumption have the most significant environmental impacts in all scenarios and all categories. The combined utilization of the UF and RO technologies in the secondary and tertiary treatment processes reduces the health damage caused by microbial diseases, which contributes significantly to reducing overall environmental damage.